Satu Kajian Teori Tentang Penyejukan Air didalam Labu Sayung - Abidin Hasan, Zainul (1986)
A theoritical study of water in labu (earthem waterjug) shows that the temperature of water in labu is slightly lower than the ambient which is mainly due to evaporation from the wall's surface of labu. The temperature difference between the water temperature and the ambient depends on the rate of evaporation which 'en tum depends on ambient temperature and humidity. It also depends on thickness of the labu's wall and the type of clayfrom which it is made.